2017
DOI: 10.1038/s41598-017-13013-y
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition affects the phylogenetic diversity and relative abundance of transcriptionally active methanogens in the bovine rumen

Abstract: Methane generated during enteric fermentation in ruminant livestock species is a major contributor to global anthropogenic greenhouse gas emissions. A period of moderate feed restriction followed by ad libitum access to feed is widely applied in cattle management to exploit the animal’s compensatory growth potential and reduce feed costs. In the present study, we utilised microbial RNA from rumen digesta samples to assess the phylogenetic diversity of transcriptionally active methanogens from feed-restricted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In rumen, Methanomicrobium converts H 2 and/or formate into CH 4 (Leahy et al, 2013). The abundance of Thermoplasmatales was also negatively correlated with Methanobrevibacter, which is consistent with previous results (Danielsson et al, 2017;McGovern et al, 2017).…”
Section: Archaeal Communitysupporting
confidence: 91%
“…In rumen, Methanomicrobium converts H 2 and/or formate into CH 4 (Leahy et al, 2013). The abundance of Thermoplasmatales was also negatively correlated with Methanobrevibacter, which is consistent with previous results (Danielsson et al, 2017;McGovern et al, 2017).…”
Section: Archaeal Communitysupporting
confidence: 91%
“…All Euryarchaeota species found in the rabbit cecum belong to genus Methanobrevibacter that encompasses different hydrogenotrophic methane-producing species. Previous studies in humans [36] and cattle [37,38] found an overrepresentation of Methanobrevibacter species in individuals submitted to feed restriction and a negative correlation between the abundance of this bacterium and body mass index. A prevalence of Methanobrevibacter species could be a positive indicator of a healthy microbiota since restricted animals showed an overrepresentation of this genus.…”
Section: Feed Restriction Modify Euryarchaeota and Some Bacteria Relamentioning
confidence: 83%
“…The abundance of Thermoplasmatales , or some members of Thermoplasmatales might also be negatively correlated to certain Methanobrevibacter spp. ( Danielsson et al, 2017 ; McGovern et al, 2017 ). Methanobrevibacter are hydrogenotrophic methanogens ( Leahy et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%